2015
DOI: 10.15805/addicta.2015.2.1.078
|View full text |Cite
|
Sign up to set email alerts
|

School Surveys on Alcohol Use in Turkey: Are They Policy Oriented?

Abstract: ÖzHalk sağlığı alanında yapılan araştırmaların alkol kontrol politikalarını yönlendirmek amacı taşımaları, bu alanla ilgili sorunları tanımlayarak dikkati gerekli noktalara çekmeleri ve çözüme ışık tutucu bilgiler sağlamaları önemlidir. Gençlerde alkollü içecek kullanımına başlamayı geciktirmenin sağlık ve sosyal gelişim üzerinde olumlu etkileri olduğu kabul edilmektedir. Çalışmamız alkol tüketimi ile ilgili 18 ve altı yaş grubunda yapılan araştırmalardan elde edilen bilgilerin, alkol kontrol politikalarını yö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The second part consisted of a questionnaire form which investigated the type of internet access of the students, the period of usage of internet, which activities in the internet they participated in and with what frequency they participated in these activities, which was established as a result of literature screening perTurk Pediatri Ars 2016; 51: [22][23][24][25][26][27][28][29][30][31][32][33][34] Çavdar et al Health behaviors in adolescents formed by the investigators and face to face interviews with the young individuals and which took its final shape as a result of a pilot study. In this study, only the time of usage of internet was included in the evaluation among these questions.…”
Section: Data Collection Tools Used In the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The second part consisted of a questionnaire form which investigated the type of internet access of the students, the period of usage of internet, which activities in the internet they participated in and with what frequency they participated in these activities, which was established as a result of literature screening perTurk Pediatri Ars 2016; 51: [22][23][24][25][26][27][28][29][30][31][32][33][34] Çavdar et al Health behaviors in adolescents formed by the investigators and face to face interviews with the young individuals and which took its final shape as a result of a pilot study. In this study, only the time of usage of internet was included in the evaluation among these questions.…”
Section: Data Collection Tools Used In the Studymentioning
confidence: 99%
“…It was observed that the rate of having experimented an alcoholic beverage was lower compared to the rate found in high school students in Istanbul (61%) and higher compared to the rate found in high school students in Samsun in 2008 (26.07%) (11,14). In a research study reviewing the studies which investigated the frequencies of consumption of alcohol in adolescents below the age of 18 years in Turkey, it was reported that the frequency of lifelong consumption of alcohol ranged between 4.4% and 65%, whereas the frequencies of consuming alcohol currently were reported to range between 6.5% and 42% in different studies conducted in different provinces in Turkey with adolescents at different ages (11,14,19,21,26,27). In this study, the rate of having experimented an alcoholic beverage was found to be lower compared to the rate found in high school students in USA in 2013 (66.2), but the fact that the rate of having drunk an alcoholic beverage at least for once in the last one month was higher compared to the rate found in USA (34.9%) draws attention to this problem (22).…”
Section: Behaviors Of Consuming Alcoholic Beveragesmentioning
confidence: 99%